Deskripsi Proses Pembuatan Karya Montase SD Negeri 74 Kota Bengkulu - Hasnawati Hasnawati; Pebrian Tarmizi; Anisya'u Khairul Umahat (JURIDIKDAS, 2019)
This study aims to describe the process of making montage work SDN 74 Bengkulu City. Types and methods used in this study are qualitative research with descriptive methods. The subjects of this study were class IVC totaling 33 students. Data collection techniques in this study in the form of observation and interviews. The results of this study are the process of making montage works starting with the preparation of montage materials, tools, base fields, and supporting materials by each group. The montage material collected has not yet been cut, so it is necessary to cut the montage material. Most groups have difficulty when arranging pieces of the picture. Gluing has been done by each group. Each group has given color to the montage created. Based on the results of the study, it can be concluded that the process of making montage works begins with preparatory steps in the form of collecting montage materials, tools, base fields and supporting materials. Then the work steps in the form of compilation of image pieces, gluing and coloring.